2021
DOI: 10.2147/ppa.s333595
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Services: Patient Satisfaction and Loyalty Lessons from Islamic Friendly Hospitals

Abstract: Background The study has aimed to investigate the Muslim patient’s psychological factors related to healthcare services that influence their loyalty intention for further treatment at private hospitals in Malaysia. Methods Data were collected from private hospitals in Klang Valley. A total of 379 responses from patients were analysed using the structural equation modelling approach. Results The findings revealed that administrative behaviour,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…Many researchers pointed that consumers’ attitudes motivate consumption behavioral intention ( Costell et al, 2010 ). Other previous literature investigated consumers’ perception and satisfaction as a significant component of consumers’ attitudes and loyalty ( Costa et al, 2020 ; Rahman et al, 2021 ). Sadiq et al (2021) reported that consumers’ attitude is a crucial dimension in determining consumption behavioral intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers pointed that consumers’ attitudes motivate consumption behavioral intention ( Costell et al, 2010 ). Other previous literature investigated consumers’ perception and satisfaction as a significant component of consumers’ attitudes and loyalty ( Costa et al, 2020 ; Rahman et al, 2021 ). Sadiq et al (2021) reported that consumers’ attitude is a crucial dimension in determining consumption behavioral intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to major deviations in the physical settings of different medical specializations and disciplines, the outcomes of previous studies on the healthcare service environment have diverged from one form of healthcare service to another (Han et al, 2018). The study of Rahman et al (2021d) is the only recent study in the Malaysian healthcare context that addresses the service environment and patients' responses which motivated this study to extend and fill the missing links and enhance the body of knowledge in the healthcare service domain.…”
mentioning
confidence: 99%
“…According to Zhou (2011), SQ considers the reliability, responsiveness, assurance, and empathy of the services provided to individuals. Rahman, Bhuiyan, et al (2021) highlighted that higher service quality improves consumers’ higher satisfaction, while Rahman, Gazi, et al (2021) discussed the effects of service quality and consumer performance. Thus, service quality can be perceived as a critical determinant of effectiveness and efficiency to assess m-commerce performance levels.…”
Section: Service Qualitymentioning
confidence: 99%